Enhanced fluorescence of phthalimide compounds induced by the incorporation of electron-donating alicyclic amino groups. Issue 23 (31st May 2018) - Orita, Ryoji; Franckevičius, Marius; Vyšniauskas, Aurimas; Gulbinas, Vidmantas; Sugiyama, Haruki; Uekusa, Hidehiro; Kanosue, Kenta; Ishige, Ryohei; Ando, Shinji
Abstract : A significant difference in fluorescence properties between 3- and 4-substituted phthalimides demonstrates the formation of excited TICT and planar ICT states, respectively. Abstract : Due to their high thermal and environmental stability, polyimides (PIs) are one of the most attractive candidates for novel highly fluorescent polymers, though photophysical studies of PIs are challenging owing to their poor solubility in common solvents. To overcome these problems, we have synthesized and examined a series of low molecular weight model imide compounds: substituted N -cyclohexylphthalimides with alicyclic amino groups at the 3 or 4-positions of the benzene rings ( x -NHPI s). Their photophysical properties were systematically investigated by steady-state UV/Visible absorption, fluorescence, and time-resolved fluorescence techniques. In solution, unsubstituted N -cyclohexylphthalimide (NHPI ) showed almost no emission, while x -NHPI s exhibited enhanced fluorescence emission depending on the solvent polarity. Analysis of the solvatochromism of the x -NHPI s via Lippert–Mataga plots indicated the generation of large dipole moments in the excited singlet states originating from the intramolecular charge-transfer (ICT) states. The significant difference in the fluorescence quantum yields ( Φ ) between the 3-substituted (3Pi and3Pyr ) and 4-substituted NHPIs (4Pi and4Pyr ) strongly suggests that the former form a twisted ICT (TICT) state, whereas the latter form a planar ICT (PICT) state when excited. 4-Substituted NHPIs also show high fluorescence yields in the crystalline state. A particularly large Φ value was obtained for the4Pi crystal, which we explain by the large intermolecular distances and the arrangement of molecules minimizing intermolecular interactions as well as the small non-radiative deactivation rate. These facts clearly demonstrate that the introduction of an alicyclic amino group intoNHPI at the 4-position enhances the fluorescence quantum yields significantly, which suggests a new pathway for the development of novel, highly fluorescent PIs.